(untitled) (Global Journal of Human-Social Science, 2024)
Starting from the assertion that vitality can be promoted by morphological elements the article focuses on the significance of understanding these relationships for the urban security The research aims to develop an original methodological essay in different scalar approaches of the Cidade Industrial de Curitiba CIC neighborhood in the state capital of Paran Brazil The study began with spatial syntax on a macroscale CIC associating road axes integration with crime spots resulting in the selection of four analysis points on the microscale street The integration of these two scales as a unique feature of the study Considering the lot frontage as a unit of evaluation for interpreting characteristics of public spaces private areas temporary conditions and nighttime scenarios the answers to the investigative question indicate similar behavior for the parameters of the two latter themes At the same time significant connections with criminal activities are found only for the second subject This result is primarily conditioned by the existence of elements that do not generate vitalized places and are not attractive to the attention of offenders In conclusion the guiding hypothesis that certain variables for vitality have more relevant relationships between landscape and security is confirmed The practical implications of this confirmation have real-world applications in structuring integrated policies for urban planning and security measures in contemporary cities